Why Disrespectful Acts against Prophet Muhammad and Quran Must be Outlawed Worldwide: An Analysis of Legislations and Case Laws (Part 1) - Hopkinson, Eckhart Christopher (International journal of multicultural and multireligious understanding, 2025)
Controversies arose much more than before after the deliberate republication of the Prophet’s Muhammad cartoons by a French weekly magazine, Charlie Hebdo in 2020. But, this article will prove that ridiculing and insulting are not instances of the right for the freedom of speech and expression. It has been discussed that publishing the insulting cartoons do not count as a defense of the right for freedom of expression. Europeans have never permitted the prosecution of Prophet Muhammad cartoons or Quran burning issues to reach the courts because they understand that if these cases were brought before the court, the judicial system would be required to restrict such actions based on their criminal laws. Even if the court ruled it as free speech, the civil parties could appeal to the European Convention on Human Rights (ECHR), and it would have to restrict those actions according to para. 2 of Article 10 of the convention, as it has previously ruled in several similar cases. If the ECHR supports such actions, the decision would be conflicting. It is evident from both a rational and moral standpoint that such actions are unjustifiable, and there is no requirement to consult the regulations of the courts in Europe or America. The approach of this article, however, aims to demonstrate that the disrespectful acts against Prophet Muhammad and the Quran should be globally outlawed. This is substantiated by examining previous worldwide courts, to illustrate that failure to prosecute such acts contradicts their principles, values, and prior judgments. This article demonstrates that if cases involving Prophet Muhammad cartoons, Quran burning, or any other form of disrespect towards them were to be brought to court, they would not be considered as free speech and would not be protected as such.